The Influence Of Electronic Word Of Mouth (E-Wom) On Maybelline Cosmetics Purchase Intention: Mediating Effect Of Brand Image And Brand Integrity - Salsabilah, Tasya; Rachmawati, Indira (eProceedings of Management, 2025)
In today’s dynamic digital environment, Electronic Word of Mouth (e-WOM) emerges as a powerful force that shapes consumer decisions—particularly in the beauty and cosmetics industry where consumer trust is crucial. This study investigates the influence of e-WOM on consumers’ purchase intention toward Maybelline cosmetics, emphasizing the mediating roles of brand image and brand integrity. Employing a quantitative approach, data were gathered from 385 active social media users in Indonesia who use Maybelline products. The data were examined utilizing Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results show that e-WOM significantly enhances both brand image and brand integrity, which in turn positively influence consumers’ purchase intentions. These mediating variables play a crucial role in strengthening the connection between online consumer conversations and actual buying behavior. The study contributes to the digital marketing literature by offering insights into how cosmetics brands can strategically leverage e-WOM to build trust, enhance brand perception, and drive purchase decisions. Practical implications suggest that consistent brand communication and ethical values, combined with effective digital engagement, are key to increasing consumer loyalty and market competitiveness. Keywords: e-WOM, Brand Image, Brand Integrity, Purchase Intention, Cosmetics.